Political Connection and Firm Value in Indonesia - Versiandika Yudha Pratama; Doddy Setiawan (Sebelas Maret Business Review, 2018)
This is an event study aims to determine the influence of political connections to firm value as measured by cumulative abnormal return on non-financial sector companies listed in Indonesia Stock Exchange. This study used secondary data in the form of stock price and annual financial statement obtained the Indonesia Stock Exchange website, Indonesian Capital Market Directory, and other relevant sources. In sampling technique, purposive sampling method is used where 272 non-financial sector companies are selected. The data is examined by using multiple linear regression to measure the influence of political connections on firm value. The findings of this study revealed that political connections have an effect on firm value as measured by cumulative abnormal return on non-financial sector companies listed in Indonesia Stock Exchange.